ACCUMULATION AND VERTICAL DISPLACEMENT OF NUTRIENTS AT IRRIGATED FRUIT GROWING AREAS - Santos Júnior, Gutemberg Pereira dos; Fraga, Vania da Silva; Araújo, Cícero Antônio de Sousa; Oliveira, Fabio Freire de; Tavares Filho, Gilberto Saraiva (Acta Biologica Brasiliensia, 2024)
The application of soluble fertilizers without planning burdens agricultural production and leads to soil salinization, a very evident problem in irrigated agriculture in the semiarid region. The soil management practices used in grape and mango cultivation are the main responsible for the loss of nutrients by leaching and soil salinization in the São Francisco submedium’ Valley. The objective of the work was to quantify the accumulation and vertical displacement of nutrients in 0-20, 20-40, 40-60, 60-80 and 80-100 cm layers of cultivated and native areas. The study was carried out in the municipality of Petrolina/PE, in 43 areas with different cultivated grapevine, mango and Caatinga crops in the São Francisco submedium’ Valley. PH, EC, OM, P, K+, Ca++ and M++ were evaluated at different depths. The movement of nutrients, especially P, was favored by the continuous application of high fertilizer doses as well as by the sandy texture of the soils studied. The high levels of nutrients observed in the areas cultivated with grapevine suggest an adjustment in the recommended fertilizer doses, aiming at the reduction of environmental impacts and fertilizer losses.